Analisis Keamanan Website Menggunakan Ptes (Penetration Testing Execution And Standart) - Delta Anugrah Utama; Khairil Khairil; Reno Supardi (UNIVED Press, 2024)
Websites are a vital element in the evolution of the internet, with more than 1.9 billion sites worldwide today. Their use was initially limited to personal purposes, but now almost all companies have websites, such as Facebook, Apple, and BBC News. Tim Berners-Lee created the first website in the late 1980s through the World Wide Web (W3) project. Penetration Testing is an evaluation method for identifying weaknesses in a security system, network, or web application. This involves direct attacks against targets under test to detect and correct weaknesses. The aim is to identify potential weak points and ensure compliance with security policies. Test results using Accuntetix show low-level system vulnerabilities on the website of min2kotabengkulu.sch.id, which can be considered quite safe from attacks.